Bridge global damage identification using vibration data - Prawin, J. (Journal of Structural Engineering, 2024)
Mode shapes are the predominant dynamic sensitive features for structural damage identification. This paper proposes a vibration-based bridge global damage identification technique using mode shape data. Two cases of global damages: increased boundary stiffness as a result of a damaged bearing and reduced foundation stiffness as a result of scouring are analyzed by the proposed vibration-based damage diagnostic technique. New damage indicators based on the shape change of the first mode shape gradient and root mean square difference of first mode shape between healthy and damaged bridge are proposed for bridge bearing and scouring damage identification. Numerical simulation studies have been carried out on two bridge models: i) single-span bridge: simply supported beam with damaged bearing supports (i.e. with varied levels of rotational spring stiffness) and ii) multi-span bridge: four simply supported beams resting on sprung piers and foundations (i.e. with varied levels of foundation spring stiffness) to demonstrate the proposed mode shape based global damage identification technique. Investigations concluded that the mode shape gradient amplifies the effect of changing support stiffness due to bridge bearing damage and serves as a better feature for bridge bearing damage identification over natural frequency change and change in mode shape amplitudes and other higher order mode shape gradients. The change in the trend of the first mode shape gradient from sigmoid shape towards an approximate sine wave shape robustly confirms the bearing seizure. The relative change of mode shape amplitudes at damaged pier and root mean square difference between healthy and scoured mode shapes confirm the bridge scouring damage. The proposed mode shape-based indicators are effective in bridge global damage identification.